Learning English for Specific Purposes through Blended Learning at Public Islamic University (A Case Study at Private University Jepara Indonesia) - Haryanto, Haryanto; Purwanto, Purwanto; Giyoto, Giyoto (Technium Social Sciences Journal, 2021)
English courses in public universities (Non-English Majors) in Indonesia are generally part of the personality development course (MPK). This study aims to describe the implementation of Blended Learning based English learning in the context of ESP in non-Major English study programs at the Nahdlatul Ulama Islamic University (UNISNU) Jepara Indonesia. This research method is descriptive qualitative. The data was obtained by interviewing the lecturers by purposive sampling and curriculum documentation as well as the syllabus of English courses that have been applied in the 2019/2020 school year in 16 study programs in 5 faculties. All course syllabi were obtained by the direct survey for the same location in one university in which the researcher categorized as primary data. The secondary data were obtained through an internet search (online). The results of the study showed that by referring to the syllabus of the study program the material English learning on the data can be grouped into five categories, namely (1) English Grammar (EG) was found in the study program (PS) 4,6,7,8,10,14 and 15; (2) General Reading Skills (GRS) was obtained in PS4,6,7,8,10,14,15; (3) The combination of English Grammar (EG) and General Reading Skills (GRS) were obtained in PS4,6,7,8,9,10,14, 15; (4) The combination of Four Skills was obtained at PS 5,9,11,12,13; and (5) Combination of Multi-Discipline Mixture English obtained in PS 1,2,3. ESP with Blended learning approach is reflected by the application of face-to-face learning model mixed with learning models with learning media in the form of e-learning as the characteristics of major fields at each faculty.